Announcement Effect of Dividends and Share Price Response: Evidence from Indian Financial Services Companies - P. Arun Prakash, M. Karthick, (European Economic Letters (EEL), 2025)
This study examines the Indian capital market's informational efficiency in relation to financial services companies' dividend announcements. The sample consists of 79 final dividend announcements from 2013 to 2024 that were examined utilizing the 21-day event window's Average Abnormal Return (AAR) and Cumulative Average Abnormal Return (CAAR). According to the results, AAR found positive 38% during window period, on the event day (Day 0) both AAR (0.004450) and CAAR (0.005959) found positive. Pre-event data reveals a range of responses, including indications of anticipatory trading and potential information leaks, especially from Day -13 to Day -2. AAR mostly went negative after the event, indicating a market correction following the initial overreaction. The CAAR was not statistically significant, although remaining positive for the majority of the intervals. Overall, the findings are consistent with the semi-strong version of market efficiency, showing that Indian stock prices react swiftly to news about dividends.